A Digital Signature Model Using XAdES Standard as a Rest Service - Renato Carauta Ribeiro; Murilo Góes de Almeida; Edna Dias Canedo (Information, 2021)
The digital signature of documents and degrees is a topic widely discussed in the Federal Public Administration. Several laws and ordinances were created to standardize the issuance, validation and legal validity of digitally signed documents in national territory, such as the ordinances created by the Ministry of Education (MEC) to regulate the issuance of degrees in digital format. These ordinances created guidelines and standards that must be adopted by Federal Universities for the signing of in digital format. The main objective of this work is to study these ordinances, the main technologies and digital signature standards used in the literature to create a digital signature system model for University of Brasília-UnB, which complies with the MEC and ICP-Brazil standards. Moreover, the model must be developed with the main standards and technologies in the market, cohesive to the current UnB architecture, easy to maintain and update to new standards that may emerge, and also be a fully open source project. An architectural model and a prototype in Java language were developed using XAdES4j library as a microservice intermediated by the bus used in UnB. The prototype developed was compared with the current digital signature system named C3Web. The comparative tests and results between the two solutions showed that the current system used in UnB does not perform the signature in accordance with the standard proposed by the MEC, in addition to being a private system using proprietary technologies for the execution of digital signatures. The tests performed with the proposed model demonstrated that it performs the digital signature in accordance with the XAdES-T standard, regulations of the MEC and ICP-Brazil. In addition, the solution presented a performance comparable to the current system used by UnB with a little more effective security than the current system used. The current model developed in this work can be a basis for the creation of future subscription systems for Brazilian Universities.